Hospital attendance patterns in long term survivors of cancer. Issue 4 (19th March 2004) - Johnson, R; Horne, B; Feltbower, R G; Butler, G E; Glaser, A W
Abstract : Aims: To identify attendance patterns in a childhood cancer long term follow up clinic, in order to inform decision making strategies for efficient, cost effective local and national surveillance of survivors. Methods: Cross-sectional review of 385 individuals >5 years from completion of cancer therapy in childhood or adolescence, attending a regional paediatric oncology and haematology centre. Results: Attenders were younger than non-attenders in the <18 age group; no differences were found for ⩾18 year age group. Those attending clinic were more recently off treatment; no significant difference existed for those <7 years from completion of therapy. A greater proportion of attenders were in the most affluent socioeconomic groups with a greater proportion of non-attenders in the lower groups. Those in full time education or training were more likely to attend and those unemployed were less likely. Multiple regression analysis confirmed a significant trend in reduction in attendance with increasing social deprivation, and that attenders were more than twice as likely to be in full time education or training. Conclusions: Following cancer treatment in childhood and adolescence, attendance at long term follow up programmes is determined by social factors including education, employment, and deprivation.